Heteromysoides taramensis, a new species of mysid (Mysida: Mysidae) from an anchialine cave on Tarama Island, Ryukyu Islands, southwestern Japan - Shimomura, Michitaka; Fujita, Yoshihisa (Zootaxa, 2020)
Heteromysoides taramensis, a new species of the family Mysidae (Mysida) is described from an anchialine cave on Tarama Island, Ryukyu Islands, southwestern Japan. This species differs from its congeners by the following combination of characters: eyes subrectangular in dorsal aspect without process; cornea developed; telson distally rounded, 1.3 times as long as maximum width, with 5 or 6 pairs of simple spines distolaterally, 1 pair of long simple spines subapically and 1 pair of short simple spines apically; antennal scale elongated elliptical, extending to distal margin of antennular peduncle; antennal sympod with distomesial corner produced into blunt tooth; and endopod of third thoracopod with simple, not subchelate, termination.